Genetically Predicted Telomere Length and Its Relationship With Alzheimer’s Disease - Yu, Guangping; Lu, Leihong; Ma, Zaihong; Wu, Shouhai (Frontiers in Genetics, 2021)
Are shorter telomeres causal risk factors for Alzheimer’s disease? This study aimed to examine if longer telomeres were causally associated with lower risk of Alzheimer’s disease using Mendelian randomization analysis. Two-sample Mendelian randomization methods were applied to the summary effect sizes and standard errors from a genome-wide association study (GWAS) for Alzheimer’s disease. Twenty single nucleotides polymorphisms (SNPs) that were of genome-wide significance were selected as instrumental variables for leukocyte telomere length. The main analyses were performed primarily using the random-effects inverse-variance weighted method and were complemented with the other three methods: weighted median approaches, MR-Egger regression, and weighted mode approaches. The intercept of MR-Egger regression was used to assess horizontal pleiotropy. We found that longer telomeres could reduce the risks of Alzheimer’s disease (odds ratio = 0.79, 95% confidence interval: 0.67, 0.93, P = 0.004). Comparable results were obtained using weighted median approaches, MR-Egger regression, and weighted mode approaches. The intercept of the MR-Egger regression was close to zero. This may show that there was not suggestive of horizontal pleiotropy. Our findings provided additional evidence regarding the putative causal association between longer telomere length and the lower risks of Alzheimer’s disease.